A systematic review of the studies that evaluate the performance of the DAPT score. Issue 10 (26th July 2020) - Kwok, Chun Shing; Wong, Chun Wai; Nagaraja, Vinayak; Mamas, Mamas A.
Abstract: Background: The Dual Antiplatelet Therapy (DAPT) score was derived to determine which patients may benefit from prolonged DAPT therapy after 12 months based on the balance between ischaemic and bleeding events. Several studies have attempted to validate the score with inconsistent findings. Methods: We conducted a systematic review of the studies that evaluated the DAPT score in PCI populations. A search was performed on MEDLINE and EMBASE and two independent reviewers reviewed the search results for study inclusion and extracted data from studies which met the inclusion criteria. Data are presented in tables and narrative synthesis was performed. Results: A total of 13 studies were included in this review. The study designs included post hoc analysis of randomised trials, prospective cohorts, retrospective cohorts and a case‐control study. In the derivation/validation study, the c‐statistic for ischaemic and bleeding outcomes were 0.64/0.70 and 0.68/0.64, respectively. Among the validation studies, the C‐statistics for composite outcomes ranged from 0.53 to 0.71 for ischaemic outcomes and 0.49 to 0.71 for bleeding outcomes. Only one study randomised patients with high DAPT score to different combinations of antiplatelet after 1 year of DAPT and found that continuation of DAPT was associated with fewer deaths because of myocardial infarction, but more bleeding. Conclusions: While not designed for this purpose many studies have shown that the DAPT score has modest predictive value for ischaemic and bleeding outcomes. A prospective randomised controlled trial is needed to evaluate the clinical benefits of utilising the DAPT score in guiding continued DAPT therapy beyond 1 year.